Pelatihan Penyusunan Arus Kas (Cashflow) Dan Pembuatan Profil Usaha Bagi Kelompok UMKM Sahabat Berdikari Mandiri - Solikhin, Agus; Syarif, Agus; Utama, Ahmad Nur Budi; SB, Istiqomah Malinda (Journal of Community Engagement Research for Sustainability, 2023)
The aim of this Community Service is to educate MSME members of Sahabat Berdikari Mandiri (SBM) about the importance of business profiles and cash flow through improving skills (direct practice) in creating business profiles and arranging cash flow independently. The continuation of Community Service is expected to increase the profitability of MSMEs by creating business operational efficiency in terms of managing cash in and cash out of the business and increasing market share (product sales). The availability of business profiles and the application of cash flow in MSME operations will be able to add economic value and income for MSME players. The method of implementing this service is by means of lectures, demonstration illustrations, training and intensive mentoring with community service participants. Training on creating business profiles and preparing cash flow is a community service activity that will be carried out at partner locations, namely at the SBM Secretariat Puri Mayang Complex and the production houses of SBM MSME members in Jambi City. The service activities were attended by MSME participants who are members of the SBM MSME Association. The participant description will include 30 MSME players from 111 registered members as of March 3 2023 with business owner status. The results of the service show that the SBM business group has the ability to create a business profile and is able to organize cash flow by utilizing digital financial applications.